(untitled) (Research, Society and Development, 2020)
In Brazil, leprosy is a serious public health problem. Goal: Identify the reasons associated with the abandonment or interruption of leprosy treatment in a Family Health Unit. Methodology: This is an exploratory, descriptive and documentary field research with a mixed approach, carried out in a Family Health Unit in the city of São Luís– MA, with 4 patients, using questionnaires and semi-structured interview script, which were recorded and transcribed in full with 4 nursing professionals, applying questionnaires. Results: They indicated that it affects men and women in the same proportion, with different age groups, with predominance in brown color / race and with low level of education and occupations, with a total income of up to 1 minimum wage, becoming factors that favor irregularity or abandonment of polychemotherapy. Conclusion: In this study, the reasons exposed by the respondents stood out: the unavailability of medication, underestimating the importance of treatment and referral to other units.